2019
DOI: 10.1016/j.ebiom.2019.09.027
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ induces stemness through non-canonical AKT-FOXO3a axis in oral squamous cell carcinoma

Abstract: BackgroundFOXO3a has been widely regarded as a tumor suppressor. It also plays a paradoxical role in regulating the cancer stem cells (CSCs), responsible for tumor-initiation, chemo-resistance, and recurrence in various solid tumors, including oral squamous cell carcinoma (OSCC). This study aims to uncover the role of FOXO3a and its importance for a non-canonical pathway of TGFβ in regulating the OSCC stemness.MethodsWe identified FOXO3a expression in OSCC tissues and cell lines using immunohistochemistry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…104 It has also been verified through an in vitro study in oral squamous cell carcinoma that TGF-β1 can enhance the CSC phenotype of cancer cells. 105 Findings in a cervical cancer study showed that TGF-β1 promoted EMT in cancer cells and helped them to obtain a CSC phenotype. 80 Similarly, in hepatocellular carcinoma, TGF-β1 could achieve the same effect as in cervical cancer by downregulating TP53INP1 through miR-155.…”
Section: Csc-associated Epithelial-mesenchymal Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…104 It has also been verified through an in vitro study in oral squamous cell carcinoma that TGF-β1 can enhance the CSC phenotype of cancer cells. 105 Findings in a cervical cancer study showed that TGF-β1 promoted EMT in cancer cells and helped them to obtain a CSC phenotype. 80 Similarly, in hepatocellular carcinoma, TGF-β1 could achieve the same effect as in cervical cancer by downregulating TP53INP1 through miR-155.…”
Section: Csc-associated Epithelial-mesenchymal Transitionmentioning
confidence: 99%
“…117 In addition, TGF-β has also been confirmed to induce oral squamous cell carcinoma cells to take on a CSC phenotype by abolishing FOXO3a. 105 Although there is an unfortunate lack of studies on the response of oral CSCs to radiotherapy to date, the results in the other cancers mentioned above suggest that the increased secretion of cytokines in the oral cancer TME following radiotherapy may contribute to the recurrence and metastasis of oral cancer postradiotherapy by enhancing CSC properties.…”
Section: Cscs and Cscs Nichesmentioning
confidence: 99%
“…They interpret their findings as significant for the identification of diagnostic biomarkers, as well as for effective treatment strategies targeting both the TGF-β and the PI3K/Akt pathways (Bian et al, 2012). Li K. et al (2019) showed that TGFβ-induced the activation of AKT rather than ERK1/2 in oral SCC and further illustrated that the non-Smad AKT-FOXO3a axis is essential to regulate the stemness of CSC. There is evidence from the results of different entities such as breast, cervical, and ovarian cancer that the canonical pathway as well as crosstalk of TGF-β are both important factors to regulate the cancer stemness (Chihara et al, 2017;Wu et al, 2017;Matsumoto et al, 2018;Li K. et al, 2019).…”
Section: Targeting Csc Signaling Pathwaysmentioning
confidence: 98%
“…In an article in EBioMedicine [9] , Li et al reported the regulation of FOXO3a on the stemness of OSCC. The team first analyzed the correlation between FOXO3a expression and the clinicalpathologic features of OSCC patients.…”
mentioning
confidence: 99%
“…Moreover, there are other kinases apart from AKT and ERK1/2 (such as SGK, CK1 and IKK) that can induce the translocation of FOXO3a between the cytoplasm and the nucleus, and these kinases can also be activated by cross-talk of TGF β. In the newly accepted article by Li et al only AKT and ERK1/2 were detected as the upstream targets [9] . It will be interesting in the future to investigate the pathological role of the non-Smad axis using animal models or OSCC patient samples and to further confirm whether other kinases also regulate the translocation of FOXO3a.…”
mentioning
confidence: 99%